Hypoglycemia. - Fagulha, A (1989)
With near optimal metabolic control, in diabetes mellitus, hypoglycaemia has become a very important problem. Its main causes are excessive insulin or sulfonylurea dosages, omission of meals, unprogrammed physical exercise or disturbances of the neurohormonal counterregulatory mechanisms.